2007
DOI: 10.1038/sj.onc.1210274
|View full text |Cite
|
Sign up to set email alerts
|

Akt activation induces epidermal hyperplasia and proliferation of epidermal progenitors

Abstract: Various common signaling pathways maintain tissue stem cells, including Notch and Wnt/b-catenin signals. Phosphoinositide-3 kinase (PI3K)/Akt signaling regulates the 'stemness' of several stem cells in culture, specifically in maintaining embryonic stem and neural stem cells, and in deriving embryonic germ cells from primordial germ cells. We examined the effect of Akt signaling in epidermal cells in transgenic mice expressing an Akt-Mer fusion protein whose kinase activity was conditionally activated by treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 30 publications
1
64
1
Order By: Relevance
“…Work here might be complicated by redundant functions of the family members of Akt1/2/3 and Tcl1 gene family. However, it is interesting to observe that in the epidermis, deletion of Akt1 causes thinner epidermal layers and retarded-HF development, whereas double mutants (Akt1 À/À Akt2 À/À and Akt1 À/À Akt3 À/À ) (Peng et al, 2003;Yang et al, 2005) show more severe defects, and transgenic mice expressing Akt-Mer fusion proteins induces epidermal hyperplasia and proliferation of epidermal progenitors leading to epidermal and follicular hyperplasia (Murayama et al, 2007). As already pointed out before, Tcl1 is involved in the normal-self renewal of ES cells (Glover et al, 2006;Matoba et al, 2006;GalanCaritad et al, 2007) and upstream genes such as transcription factor Oct4, which directly activates Tcl1 in ES cells and is expressed in human HFs (Yu et al, 2006), should also be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Work here might be complicated by redundant functions of the family members of Akt1/2/3 and Tcl1 gene family. However, it is interesting to observe that in the epidermis, deletion of Akt1 causes thinner epidermal layers and retarded-HF development, whereas double mutants (Akt1 À/À Akt2 À/À and Akt1 À/À Akt3 À/À ) (Peng et al, 2003;Yang et al, 2005) show more severe defects, and transgenic mice expressing Akt-Mer fusion proteins induces epidermal hyperplasia and proliferation of epidermal progenitors leading to epidermal and follicular hyperplasia (Murayama et al, 2007). As already pointed out before, Tcl1 is involved in the normal-self renewal of ES cells (Glover et al, 2006;Matoba et al, 2006;GalanCaritad et al, 2007) and upstream genes such as transcription factor Oct4, which directly activates Tcl1 in ES cells and is expressed in human HFs (Yu et al, 2006), should also be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, the key hair-related findings in this sonic stress model were reproduced in a classical foot shock stress model (Katayama et al, 2007). Importantly, when microdissected, organ-cultured human scalp HFs are directly exposed to NGF or substance P, very similar HF responses are seen in this human in vitro system as in Page 13 of 38 A c c e p t e d M a n u s c r i p t 13 sound-stressed mice: Inhibition of hair matrix keratinocyte proliferation, up-regulation of matrix apoptosis, increased mast cell numbers and degranulation in the CTS, and premature catagen development (Peters et al, 2006 b;Peters et al, 2007).…”
Section: Insights On Hfesc Endocrinology From Mouse Geneticsmentioning
confidence: 98%
“…Subsequent studies in mice revealed that perceived stress challenge shortens the hair cycle growth phase (anagen) and prematurely induces catagen. Furthermore, these studies revealed that the major stress-associated growth factor, NGF, in conjunction with the prototypic stress-associated neuropeptide, substance P, and with skin mast cells (as "central switch-boards of neurogenic inflammation") could be identified as key mediators in the stress-induced perifollicular neurogenic inflammation (Arck et al, 2003; Joachim et al, 2007;Peters et al, 2004).Essentially, the key hair-related findings in this sonic stress model were reproduced in a classical foot shock stress model (Katayama et al, 2007). Importantly, when microdissected, organ-cultured human scalp HFs are directly exposed to NGF or substance P, very similar HF responses are seen in this human in vitro system as in Page 13 of 38 A c c e p t e d M a n u s c r i p t 13 sound-stressed mice: Inhibition of hair matrix keratinocyte proliferation, up-regulation of matrix apoptosis, increased mast cell numbers and degranulation in the CTS, and premature catagen development (Peters et al, 2006 b;Peters et al, 2007).…”
mentioning
confidence: 92%
“…Further experiments will be required to examine this hypothesis. It has been shown that activation of AKT can lead to the development of hyperplasia and intraepithelial neoplasia in a number of organs in transgenic mouse models [23,24]. Future studies on rapamycin and its analogues should therefore include investigations of rapamycin-induced activation of AKT in normal tissues and assess how this may affect tumourgenicity.…”
Section: Discussionmentioning
confidence: 99%